Research Mechanism of Formation on Transverse Corner Cracks in the Continuous Casting Slab of Peritectic Steel. Issue 11 (26th August 2022) - Zhou, Qinghai; Yin, Yanbin; Liu, Zhiming; Zhang, Jiongming; Zhang, Jiazheng
Abstract : To figure out the formation mechanism of transverse corner cracks at the inner and outer arc of peritectic steel slab, the metallurgical microscope, scanning electron microscope with energy‐dispersive X‐ray spectroscopy, and electron probe‐X‐ray microanalysis, are used to study cracks. High‐temperature mechanical properties and the stress distribution of the outer arc of the bending section under different roll gap schemes are studied and simulated. The outer arc cracks expand along the grain boundary, while the inner arc cracks not only extend along the grain boundary but also traverse along the grains. The outer arc cracks are mainly generated at the bending section and are formed and expanded along the ferrite film. The inner arc cracks' cracking temperature is higher than the temperature of austenite transformation to ferrite. The third brittle temperature ranges are 650–850 °C, and the transverse corner crack sensitivity zone is 680–837 °C. The inner arc cracks are generated because of the element segregation and low temperature of the corner and then extended at the straightening section, and new cracks exist. The weakened cooling intensity and bending earlier at the bending section help to reduce the equivalent stress on the slab. The optimized experiments are conducted, and the transverse corner cracks are reduced significantly. Abstract : The transverse cracks of the peritectic steel slabs are generated in the secondary cooling zone, and the outer arc cracks are mainly generated in the bending section. Weak cooling and earlier bending are beneficial; the inner arc cracks are due to element segregation, precipitates, and the lower temperature at the straightening section. Optimized secondary cooling is beneficial.